Design and develop android application of fluid kinematics - Muhammad Izzat Hafiz, Ayub (2012)
This thesis would be about a Smart Phone Application on the Android platform that will open a new gateway for students to learn Fluid Mechanics in the most accessible way. The objective of this thesis is to design and developed an android application of Fluid Kinematics EBook and calculator. The application is been design and develop using MIT AppInventor. One of the core subjects for mechanical engineering student is Fluid Mechanics and one of the subtopic in the fluid mechanics is fluid kinematics. This application is just covered the studies based on diploma mechanical students. The application contain of introduction, notes, video, question examples, answers, manual solution, and calculator to solve the example question. The survey has been done after the application has been tested. The survey is done to 50 students and 20 lecturers in mechanical engineering faculty. The improvement has been made based on the recommendations from the respondent. The results of testing the application discussed in the thesis. Finally, in conclusion the objective designing and develop the application was reached.